The Relationship Of Creative Entrepreneurship Product Learning Results With The Entrepreneurial Character Of Students Of Smkn 6 Padang - Hafifah, Hasyiati; Yulastri, Asmar; Andriani, Cici; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by the low learning outcomes and entrepreneurial character of SMK N 6 Padang students. This study aims to determine whether there is a relationship between the learning outcomes of Creative Products and Entrepreneurship with the entrepreneurial character of SMKN 6 Padang students. This type of research is quantitative descriptive with a correlational approach. The population in this study was grade XI students of SMK Negeri 6 Padang, totaling 454 students. Sampling using the Proportionate Random Sampling technique, the sample amounted to 82 students. The data collection technique uses the distribution of questionnaires through google forms that have been tested for validity and reliability. Data analysis techniques use descriptive and correlational analysis. The resultsshowed that 1) Student learning outcomes were in the medium category with a range of 63 – 80 (43.90%), 2) Student entrepreneurial character was in the medium category with a range of 144 – 156 (36.58%), 3) Therewas a positive and significant relationship between the learning outcomes of Creative Products and Entrepreneurship with the entrepreneurial character of SMKN 6 Padang students with shows the significance of the relationship between learning outcomes and entrepreneurial character is 0.000 < 0.05 and the correlation value of RXY 0.626 which is considered strong and the value of Tcalculate (7,184) > Ttabel (1,664).